Recent progress of Bi-based electrocatalysts for electrocatalytic CO2 reduction. Issue 22 (30th May 2022) - Xia, Dong; Yu, Huayang; Xie, Huan; Huang, Peng; Menzel, Robert; Titirici, Maria Magdalena; Chai, Guoliang
Abstract : Both unary Bi and binary BiSn catalysts exhibit high faradaic efficiencies toward the production of formic acid via electrocatalytic CO2 reduction approach. The electrocatalytic abilities are directly related to the structures and morphologies of the metal-based catalysts. Abstract : To mitigate excessively accumulated carbon dioxide (CO2 ) in the atmosphere and tackle the associated environmental concerns, green and effective approaches are necessary. The electrocatalytic CO2 reduction reaction (CO2 RR) using sustainable electricity under benign reaction conditions represents a viable way to produce value-added and profitable chemicals. In this minireview, recent studies regarding unary Bi electrocatalysts and binary BiSn electrocatalysts are symmetrically categorized and reviewed, as they disclose high faradaic efficiencies toward the production of formate/formic acid, which has a relatively higher value of up to 0.50 ·per kg and has been widely used in the chemical and pharmaceutical industry. In particular, the preparation methodologies, electrocatalyst morphologies, catalytic performances and the corresponding mechanisms are comprehensively presented. The use of solid-state electrolytes showing high economic prospects for directly obtaining high-purity formic acid is highlighted. Finally, the remaining questions and challenges for CO2 RR exploitations using Bi-related electrocatalysts are proposed, while perspectives and the corresponding strategies aiming to enhance their entire catalytic functionalities and boost their performance are provided.